Targeting acid sphingomyelinase reduces cardiac ceramide accumulation in the post-ischemic heart. (April 2016) - Klevstig, Martina; Ståhlman, Marcus; Lundqvist, Annika; Scharin Täng, Margareta; Fogelstrand, Per; Adiels, Martin; Andersson, Linda; Kolesnick, Richard; Jeppsson, Anders; Borén, Jan; Levin, Malin C.
Abstract: Ceramide accumulation is known to accompany acute myocardial ischemia, but its role in the pathogenesis of ischemic heart disease is unclear. In this study, we aimed to determine how ceramides accumulate in the ischemic heart and to determine if cardiac function following ischemia can be improved by reducing ceramide accumulation. To investigate the association between ceramide accumulation and heart function, we analyzed myocardial left ventricle biopsies from subjects with chronic ischemia and found that ceramide levels were higher in biopsies from subjects with reduced heart function. Ceramides are produced by either de novo synthesis or hydrolysis of sphingomyelin catalyzed by acid and/or neutral sphingomyelinase. We used cultured HL-1 cardiomyocytes to investigate these pathways and showed that acid sphingomyelinase activity rather than neutral sphingomyelinase activity or de novo sphingolipid synthesis was important for hypoxia-induced ceramide accumulation. We also used mice with a partial deficiency in acid sphingomyelinase ( Smpd1 +/− mice) to investigate if limiting ceramide accumulation under ischemic conditions would have a beneficial effect on heart function and survival. Although we showed that cardiac ceramide accumulation was reduced in Smpd1 +/− mice 24 h after an induced myocardial infarction, this reduction was not accompanied by an improvement in heart function or survival. Our findings show that accumulation of cardiac ceramides in the post-ischemic heart is mediated by acid sphingomyelinase. However, targeting ceramide accumulation in the ischemic heart may not be a beneficial treatment strategy. Highlights: Ceramide accumulation in post-ischemic human heart associates with heart function. Ceramide accumulation is mediated by acid sphingomyelinase. Normalizing ceramide levels in the post-ischemic heart does not improve function and outcome.